Evaluating and Ranking Safety Risks of Isfahan Municipality Construction Projects Using Taxonomic Techniques and Risk Breakdown Structure Approach - Amir Hossein NADALI JELOKHANI; Sayyed Rasool AGHA DAVOOD; Mehdi KARBASSIAN; Abdul Majid ABDUL BAGHI (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Considering the extensive workload of construction projects in the municipality and allocating more than 70% of the approved budget to it, identifying the factors affecting their safety is very important. Therefore, this study aimed to evaluate and rank the safety risks of the construction projects of Isfahan municipality. Methods: This descriptive-analytic study was conducted in 1396. In this study, the levels of Risk Breakdown Structure, components and criteria affecting the safety risks of municipal projects were determined by semi-structured interview and a researcher-made questionnaire from 30 managers and experts of Isfahan municipality. Then, prioritizing the risks was done using the taxonomic technique and the data were analyzed using Spss20 and Excel2010 software. Results: The Risk Breakdown Structure was designed at three levels of zero level: the model title, level one: safety risk categories in the form of 7 subsets, and level 2:34 safety risks. The lowest and highest ICC experts' agreement index was 0.803 and 0.975, respectively. The average risk rating for risks prior to the implementation of the project was obtained 6, the process and the internal 8.3, the beyond-project 10, during the project implementation 17.6, the external 20.3, after implementing the project 20.4, and the support 28.2. Conclusion: According to the obtained risk factors, the safety risks in Isfahan Municipality construction projects are very important and improvement of safety in urban projects is considered as one of the main priorities of metropolitan cities. Moreover, these risks, due to their effects, directly or indirectly affect the time, cost, quality, and scope of the project.